Aktualisasi Dakwah Wasathiyah Majelis Ulama Indonesia (MUI) Pada Masyarakat Multikultural Dalam Menumbuhkan Sikap Toleransi Di Kota Makassar - Masri, Abdul Rasyid; Muhammad Mirwan; Andi Syahraeni (Jurnal Dakwah Tabligh, 2024)
Da'wah is a communication process that is based on trust (belief) and aims to invite people to carry out the provisions of Allah SWT. Where the city of Makassar, which has a multicultural society, is a challenge for the Indonesian Ulema Council (MUI) in delivering its lectures to mad'u, especially the Muslim community. The type of research used in this research is qualitative research. While this type of research uses participatory action research (PAR). Determination of informants selected by purposive technique. Data collection was carried out using interview, observation, and documentation techniques. While the validity of research data using source triangulation and method triangulation. The result of this research is that the Indonesian Ulema Council (MUI) of Makassar City has done several forms of actualization of da'wah in multicultural society, namely delivering its da'wah in a humane way to all Muslim communities, so that the delivery of its da'wah can be accepted by every community.